2020
DOI: 10.1111/1471-0528.16365
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal compared with intramuscular progestogen for preventing preterm birth in high‐risk pregnant women (VICTORIA study): a multicentre, open‐label randomised trial and meta‐analysis

Abstract: Objective To compare the efficacy of two types of progestogen therapy for preventing preterm birth (PTB) and to review the relevant literature. Design A multicentre, randomised, open‐label, equivalence trial and a meta‐analysis. Setting Tertiary referral hospitals in South Korea. Population Pregnant women with a history of spontaneous PTB or short cervical length (<25 mm). Methods Eligible women were screened and randomised at 16‒22 weeks of gestation to receive either 200 mg of vaginal micronised progesterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, they studied the majority of patients for 15 weeks assessing cervical length changes and found no significant difference between both the interventions. Moreover, Choi et al [ 25 ] conducted recent RCT comparing vaginal micronized progesterone to intramuscular 17OHPC and concluded equal efficacy for preventing PTB before 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they studied the majority of patients for 15 weeks assessing cervical length changes and found no significant difference between both the interventions. Moreover, Choi et al [ 25 ] conducted recent RCT comparing vaginal micronized progesterone to intramuscular 17OHPC and concluded equal efficacy for preventing PTB before 37 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that have been published comparing the two forms of progesterone are similarly limited by either small sample size or lack of generalizability. 9,10,12,13 One of our hypotheses at the outset of the study was that the association between route of progesterone administration and PTB might be modified by maternal BMI. Among women receiving 17OHP-C for prevention of recurrent PTB, lower plasma concentrations of 17OHP-C are associated with higher rates of prematurity, 26 and prior research has suggested that there may be an inverse relation between maternal BMI and plasma 17OHP-C concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies found either a reduction in PTB rates with vaginal progesterone 8,9 or no clinically relevant difference. [10][11][12][13] Yet, the quality of this evidence is low, owing in part to the small sample sizes, 14 and lack of generalizability to women in the United States. 15 Given the limitations of the prior studies, further research directly comparing vaginal progesterone and 17OHP-C is needed to better determine the optimal route of administration of progesterone in women with a prior PTB.…”
mentioning
confidence: 99%
“…When earlier models to predict sPTD using serum biomarkers were evaluated, they generally indicated that the association of maternal characteristics with serum biomarkers increased the ability to predict preterm delivery [21,36]. Previous preterm delivery had a strong association with preterm delivery in many previous studies, which also recommended the administration of progesterone to reduce the risk of preterm delivery [10,[60][61][62][63]. Thus, combining a history of previous preterm with serum biomarkers can increase the rate of prediction of sPTD, as found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of such preterm delivery costs can create serious nancial burdens, especially in developing countries [6,7]. There is a method available to prevent preterm births in at-risk pregnant women, such as progesterone administration but indicated only in women who had history of spontaneous preterm delivery (sPTD) [8][9][10][11][12]. Currently there is no effective universal screening method for predicting preterm delivery [13,14] .…”
Section: Introductionmentioning
confidence: 99%